The introspective cinematographer's eye in the pieces we keep - Fendi Yasuda Jamil (Nanyang Technological University, 2021)
This report is a documentation of the cinematographer's learning journey and a deeper look at the art of the cinematography in the film The Pieces We Keep. It explains his process and learning journey as the cinematographer from the development stage in pre-production to achieving the final look in production and post-production.